Time-resolved synchrotron tomographic quantification of deformation during indentation of an equiaxed semi-solid granular alloy - Cai,B; Lee,PD; Karagadde,S; Marrow,TJ; Connolley,T (Acta Materialia, 2016)
Indentation is a well-established technique for measuring mechanical properties, such as hardness and creep, in solid materials at a continuum level. In this study, we performed indentation of a semi-solid granular alloy with an equiaxed dendritic microstructure. The resulting microstructural effects were quantified using a novel thermo-mechanical setup combined with 4D (three spatial dimensions plus time) synchrotron tomography and digital volume correlation. The experiments not only revealed the multitude of deformation mechanisms occurring at a microstructural level, (e.g. dilatancy, liquid flow, macrosegregation, shrinkage voids, and intra-granular deformation), but also allowed quantification of the evolution of the strain fields within the material. The resulting methodology is a powerful tool for assessing the evolution of localized deformation and hence material properties.